2017
DOI: 10.14791/btrt.2017.5.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Analysis of Clinical Outcomes Following Stereotactic Radiosurgery for Central Neurocytoma

Abstract: Central neurocytoma (CN) typically presents as an intraventricular mass causing obstructive hydrocephalus. The first line of treatment is surgical resection with adjuvant conventional radiotherapy. Stereotactic radiosurgery (SRS) was proposed as an alternative therapy for CN because of its lower risk profile. The objective of this systematic analysis is to assess the efficacy of SRS for CN. A systematic analysis for CN treated with SRS was conducted in PubMed. Baseline patient characteristics and outcomes data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 66 publications
1
31
0
1
Order By: Relevance
“…Central neurocytoma is rare neuroepithelial tumor that is usually located in intraventricular locations near the foramen of Monro. [1,15] Central neurocytomas usually occur in the lateral ventricle, with only 3% isolated to the third ventricle. [4] The previous literature report that these tumors are usually found in young adults, with a median age between 25 and 30 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Central neurocytoma is rare neuroepithelial tumor that is usually located in intraventricular locations near the foramen of Monro. [1,15] Central neurocytomas usually occur in the lateral ventricle, with only 3% isolated to the third ventricle. [4] The previous literature report that these tumors are usually found in young adults, with a median age between 25 and 30 years.…”
Section: Discussionmentioning
confidence: 99%
“…Although standard treatment for central neurocytoma is complete surgical resection, it is difficult to remove the tumor completely because of its location. [15] Recent studies have suggested that stereotactic radiosurgery is an effective treatment modality because radiosurgery has the advantage of preserving normal brain tissues and delivering high doses of radiation to specified lesions compared with other radiotherapies. According to a recent systematic analysis, patients who underwent GKR alone had a survival rate of 98% at a mean follow-up of 62.4 months.…”
Section: Discussionmentioning
confidence: 99%
“…In a series of 14 patients treated to a mean tumor margin dose of 12.1 Gy there was a mean reduction in tumor volume by 69% at 65 months with neither tumor recurrence nor radiotherapy toxicity. 59,60 In patients with recurrent disease not suitable for further surgery or radiotherapy, chemotherapy may be an option using combinations of platinum, etoposide, topotecan, and cyclophosphamide. 53…”
Section: Central Neurocytoma (Cn)mentioning
confidence: 99%
“…On computed tomographies, CNs appear heterogeneously hyperdense with contrast enhancement while on magnetic resonance imaging; they are isointense on T1-weighted images and slightly hyperintense on T2-weighted images with vivid contrast enhancement [12]. These features may be confused with other intraventricular tumors especially ependymomas, oligodendrogliomas, and subependymal astrocytomas even after histopathology.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical gross total resection is now considered the gold standard treatment for CNs that can be achieved in 30-50% of cases with a reported 99% 5-year survival rate that came down to 86% when subtotal resection was performed [5,7,12]. The proximity to the deep critical structures and high vascularity make the achievement of such goal a real challenge.…”
Section: Introductionmentioning
confidence: 99%